Gestos e jogos: reflexões e desenvolvimento de um sistema de detecção de gestos baseado em Wearables para controle de jogos - Santos, Ezequiel França dos (2022)
This research has as general objective to develop a study on the use of wearables in games, particularly the detection of gestures to use as input devices in games, contemplating the fundamentals involved, algorithms used, and game design analysis, ergonomics, and social aspects in the approach. We present the modelling of the gesture detection algorithm using neural networks and reporting the process of development and experimentation of hardware and software, their architecture, and integration. The justification for this investigation is the possibility of exploiting an unconventional interface for the control of games and the scarcity of debate about specific wearables from the same perspective. In addition, with the rise in wearables and the digital game development industry, there is space to explore the theme. One motivation for the research started with developing an open-source project, a library for the acquisition of the shaking movement of the Apple Watch since within the standard libraries of the operating system watchOS, this resource does not exist. Furthermore, we verified that the wearables interfaces are not limited to micro-interactions, opening others possibilities like data acquisition and pattern detection with this project. Thus, the choice of developing a wearable control system for this project also aims to promote the applicability of these technologies in digital games